(2-Methylphenyl)(phenyl)methanol - Siddaraju, B.P.; Yathirajan, H.S.; Narayana, B.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(14)H(14)O, the two benzene rings are almost orthogonal [dihedral angle = 87.78 (8) degrees]. The hydroxy group lies approximately in the plane of its attached benzene ring [O-C-C-C torsion angle = -17.47 (17)degrees], and the hydroxyl and methyl groups lie to the same side of the molecule and are gauche to each other. In the crystal, a hexameric aggregate mediated by a ring of six O-H...O hydrogen bonds occurs, generating an R 6 (6)(12) loop.